Structured Reporting in Radiology - Fatehi, Mansoor; Pinto dos Santos, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides practitioners and scientists with insights into diverse aspects of structured reporting to allow them to develop tools and a knowledge base to ensure that this electronic reporting trend is widely applied. After an introduction to reporting in radiology, various parts of structured reporting are discussed in detail, including an overview of standardized reporting systems, standardized reporting language, DICOM structured reporting, template based structured reporting, and modular reporting. The last chapter addresses the interaction of structured reporting with artificial intelligence and its impact on the future of radiology. The last chapter addresses the interaction of structured reporting with artificial intelligence and its impact on the future of radiology. Endorsed by the European Society of Medical Imaging Informatics (EuSoMII), the scope of the book is based on the Medical Imaging Informatics sub-sections of the European Society of Radiology (ESR) European Training Curriculum Level I and II. It is a valuable resource for residents, radiologists and students.
Introduction to reporting in radiology -- Basics of structured reporting -- Standardized reporting systems -- Standardizing reporting language -- Interoperable reporting standards -- Template based structured reporting -- Common data elements and modular reporting -- Multimedia-enhanced structured reporting -- Strucrtured reporting and artificial intelligence -- Structured reporting beyond radiology.
Keywords: Radiology; Medical informatics; Radiology; Health Informatics; Health Informatics; Radiology Information Systems; Medical Records -- standards; Decision Making, Computer-Assisted